Hydrological characteristics assessment of Jalauar river system and its bottom sediments, Province of Iloilo, Panay island - Golez, Nelson V. (Siliman Journal, 2010)
Rivers are important to civilization because river water can be diverted for agricultural irrigation, industry, hygiene, and related uses. Most rivers have varied hydrological characteristics like water depth, flow rate and volume discharges when measured during the wet and dry season. In addition, rivers do carry dissolved minerals and organic compounds. A hydrologic monitoring was done in strategic sampling points along the river to cover the upstream (Banban, Pequeño, Calinog), midstream (Moroboro, Dingle) with sub-points before and after the dam (Imbang Pequeho—near Passi Sugar Central and Licuan, Dingle next to the National Power Corporation) and downstream (Nabitasan, Leganes) sections of the Jalaur River. Sampling was done three times per season (dry and wet seasons) at each of the five sampling sites.